Stress resistance as a way to extend active longevity - Erkomaishvili I.V. ,; Semenova G.I. ,; Pshenitsyn K.K. ,; Gerish M.D. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to study students’ awareness of stress resistance and ways to increase it in the context of prolonging active longevity. Methods and structure of the study. During the study, a survey was conducted (N=106), participants of the X Olympiad of students in the specialty “Physical Culture and Sports”, as well as students from Yekaterinburg studying in the field of “Physical Culture”. The questionnaire, along with general information about students, contained questions whose purpose was to identify the respondents’ attitude to stress resistance as a factor in prolonging active and healthy longevity. Results and conclusions. Using a survey, students' attitudes toward stress resistance as a predictor of active longevity were assessed. It was found that the most important components of maintaining a stress-resistant state, according to respondents, are: healthy sleep, physical activity and positive thinking. Factors that least reflect stress resistance are: meditation, changing the type of activity and breathing exercises. Most respondents daily use in their lives ways to achieve active longevity that directly affect increased stress resistance, such as physical activity, positive thinking, and socialization. Factors that negatively affect the stress resistance of respondents in everyday life are: problems in professional sports activities, unhealthy sleep, negative thinking, problems in the family.